Ectopic Pregnancy Risk Factors Presentation and Management Outcomes - Suliman, Awadalla Abdelwahid; Ahmed, Hajar Suliman Ibrahim; Adam Hammad, Kabbashi Mohammed; Alsiddig, Ibtehal Jaffer Youssef; Abdelgader, Mohamed Abdalla Elamin; Elhag, Abdallah Omer Elzein; Ibrahim, Safa Mohamed (Clinical Journal of Obstetrics and Gynecology, 2023)
Background: Ectopic pregnancy (EP) is a common and serious early pregnancy problem with a significant morbidity rate and the potential for maternal death. Women commonly present with minimal vaginal bleeding and abdominal pain. Objective: The main objective of the study was to evaluate the risk factors, clinical presentation, sites, and management outcomes of ectopic pregnancies. Methodology: It was a prospective descriptive, cross-sectional hospital-based study conducted at Bashair Teaching Hospital during the period January 2021–June 2021. An interview questionnaire was used, and eighty-two (82) women were included after informed consent. Demographic and clinical data concerning personal history, symptoms of presentation, risk, site, and type of management were recorded. Results: Ectopic pregnancy incidence was 2% and most risk factors were infection 29.3%, surgery 15.9%, miscarriage 13.4%, infertility 12.2%, tubal surgery 4.9%, previous ectopic pregnancy 4.9%, intrauterine contraceptive device (IUCD) 3.6%, and tubal ligation 2.4%. Women presented with bleeding and abdominal pain at 47.5%, bleeding at 18.3%, abdominal pain at 9.7%, and shock at 8.5%. The sites are ampullary (57.3%), fimbria (9.7%), interstitial (8.5%), isthmus (8.5%), ovarian (7.3%), cervical (4.8%), and abdominal (3.6%). Surgical management was 93.9%, medical and surgical management was 3.6% and medical management was 2.4%. A blood transfusion was received at 37.8%. Conclusion: The study concluded that women of reproductive age are at risk of ectopic pregnancy, so healthcare providers and doctors should have a high index of suspicion, prompt diagnosis, and intervention for ectopic pregnancy. Assessment of women at risk factors and modifications will reduce incidence.